An observational study on gray matter volume and white matter integrity in suicide attempters with bipolar I disorder - Anuranjan Vishwakarma; Pankaj; Raman Deep; S Senthil Kumaran; Pratap Sharan (Indian Journal of Psychiatry)
Background: Bipolar disorder (BD) is associated with a high risk of lifetime suicide attempts, but relatively few neuroimaging studies have investigated suicidality in the context of BD. Aim: The study aimed to assess the white matter (WM) integrity and gray matter (GM) volume associated with suicide attempts in BD. Method: This observational study recruited 32 patients with DSM-5 bipolar I disorder. Group I had multiple (≥2) lifetime suicide attempts, with at least one attempt in the past year. Group II comprised nonattempters/nonideators who screened negative on the C-SSRS-lifetime version. All patients were euthymic (≤8 on 17-item HAM-D; ≤4 on YMRS). Study assessments included a clinical proforma, NIMH-Life Chart Method, and Barratt’s Impulsivity Scale (BIS). MR imaging was performed using a 32‐channel head coil on a 3T-MR scanner. All participants underwent DTI, and images were processed using tract-based spatial statistics (TBSS). Results: The study groups were comparable for age, gender, total BIS, and illness variables. The mean age was 34.3 years (SD 10.4), with 62.5% males in group I. Group comparisons for FA value revealed a lower WM anisotropy for five clusters (threshold of FA 0.2; P < 0.001; GRF corrected) in the suicide attempters’ group. These included the left and right inferior fronto-occipital fasciculus (IFOF), left superior longitudinal fasciculus (SLF), cingulate, and forceps minor. Voxel-wise analysis of GMV did not show any significant group differences. Conclusion: The findings indicate white matter disruptions associated with lifetime suicide attempts in BD, particularly in the bilateral IFOF, left SLF, cingulate, and forceps minor.